Lubricant composition and application

By using solid-liquid collaborative lubricant compositions in the drilling fluid, the problem of lubrication failure of existing lubricants under high temperature, high density and high salinity conditions is solved, and the efficient extreme pressure lubrication performance of the drilling fluid is achieved.

CN119432335APending Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411132924.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing lubricants show lubrication failure under extreme pressure conditions of high temperature, high density and high salinity drilling fluid, which is difficult to meet the demand for efficient lubrication in the oil drilling industry.

Method used

A lubricant composition is developed, including solid lubricants and liquid lubricants, with the water contact angle of the solid lubricant greater than 90° and the extreme pressure lubricant of the liquid lubricant less than 0.15, and the lubricating performance is enhanced through the solid-liquid collaborative lubricating mechanism.

Benefits of technology

It significantly reduces the extreme pressure lubrication coefficient of the drilling fluid, improves lubrication performance, and maintains a good lubrication effect under high temperature, high pressure and high salinity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432335A_ABST
    Figure CN119432335A_ABST
Patent Text Reader

Abstract

The invention provides a lubricant composition and application thereof. The lubricant composition provided by the invention comprises a solid lubricant and a liquid lubricant, and the water contact angle of the solid lubricant is more than 90 degrees; the extreme pressure lubrication coefficient of the liquid lubricant is less than 0.15. By controlling the water contact angle of the solid lubricant, the solid lubricant has proper hydrophobic property, and when the solid lubricant is combined with a liquid lubricant with a specific extreme pressure lubrication coefficient, the adhesive force of the liquid-phase lubricant on the surface of the hydrophobic solid lubricant in a water-phase environment can be enhanced, so that the solid-liquid synergistic lubrication property is exerted. The lubricant composition has the advantages of high temperature resistance, high pressure resistance, saturated salt pollution resistance and the like, and the extreme pressure lubrication coefficient of the drilling fluid can be obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling fluid in the petroleum drilling industry, and in particular to a lubricant composition and application thereof. Background Art

[0002] In the oil drilling industry, horizontal well drilling technology can increase the contact area between the wellbore and the reservoir, which is conducive to increasing the production of a single well and realizing the transformation from multiple wells with low production to fewer wells with high production. However, during horizontal well drilling, the drill bit is close to the well wall under the action of its own weight, which increases the contact area between the drill bit and the formation, resulting in a significant increase in friction resistance during drilling. At the same time, as the extension length of horizontal wells continues to increase and the complexity of the oil and gas burial environment has greatly increased, extremely stringent requirements have been placed on the extreme pressure lubrication performance of drilling fluids under conditions of high temperature, high density, and high salinity.

[0003] Lubricants are key treatment agents for improving the lubrication performance of drilling fluids. Existing lubricants are mainly divided into two categories: solid-phase lubricants and liquid-phase lubricants. Among them, solid-phase lubricants reduce friction by converting dry friction between friction pairs into rolling friction or sliding between lamellar solid layers. They have the advantages of strong temperature resistance, good pressure resistance and excellent compatibility in drilling fluids. However, since their friction form is still solid-solid friction, the degree of improvement in lubrication effect is limited; liquid-phase lubricants can convert dry friction between friction pairs into friction between lubricating films or non-polar groups of lubricants, and have excellent friction and drag reduction effects. However, the structure of the lubricating film is destroyed under high temperature and extreme pressure, and the amount of lubricant adsorbed on the barite surface at high density is too large, which limits its adsorption at the interface of the friction pair, resulting in lubrication failure.

[0004] How to overcome the problems of existing lubricants and develop lubricants that can improve the extreme pressure lubrication properties of high-temperature, high-density, and high-salinity drilling fluids is an important research direction at present. Summary of the invention

[0005] The invention provides a lubricant composition, which has the advantages of high temperature resistance, high pressure resistance, resistance to saturated salt pollution, etc., and can significantly reduce the extreme pressure lubrication coefficient of drilling fluid.

[0006] The invention also provides a drilling fluid having a lower extreme pressure lubrication coefficient.

[0007] A first aspect of the present invention provides a lubricant composition, comprising a solid lubricant and a liquid lubricant, wherein the water contact angle of the solid lubricant is >90°;

[0008] The extreme pressure lubrication coefficient of the liquid lubricant is less than 0.15.

[0009] The lubricant composition as described above, wherein the roughness of the solid lubricant is 10 to 400 nm.

[0010] The lubricant composition as described above, wherein the surface energy of the solid lubricant is less than 54.8 mN·m.

[0011] In the lubricant composition as described above, the solid lubricant is modified graphite, and the modifier includes at least one of hydroxyl-containing nanoparticles and a silane coupling agent.

[0012] The lubricant composition as described above, wherein the liquid lubricant comprises a fatty acid derivative and a nonionic surfactant.

[0013] The lubricant composition as described above, wherein the fatty acid derivative comprises at least one of fatty acid esters, fatty acid amides, sulfurized fatty acid esters, sulfurized fatty acid amides, fatty acid amide phosphates, fatty acid polyoxyethylene ethers, and fatty acid polyoxypropylene ethers;

[0014] And / or, the nonionic surfactant includes at least one of Span and Tween.

[0015] The lubricant composition as described above, wherein it further comprises at least one of mineral oil and thickener;

[0016] The volume proportion of the mineral oil in the lubricant composition is 10% to 50%;

[0017] The mass proportion of the thickener in the lubricant composition is 1% to 5%.

[0018] The lubricant composition as described above, wherein the modified graphite is prepared by a preparation method comprising the following process:

[0019] dispersing graphite and a cationic surfactant in a solvent to obtain a graphite dispersion;

[0020] The pH of the graphite dispersion is adjusted to 10-11 and the temperature is adjusted to 40-60° C., and hydroxyl-containing nanoparticles and / or silane coupling agents are added to react for 4-6 hours.

[0021] In the lubricant composition as described above, the mass ratio of the graphite, the cationic surfactant, the hydroxyl-containing nanoparticles and the silane coupling agent is (8-10): (0.1-0.5): (0-2): (0-1).

[0022] A second aspect of the present invention provides a drilling fluid, which comprises the above lubricant composition and conventional drilling fluid.

[0023] Furthermore, the mass ratio of the lubricant composition to conventional drilling fluid is 0.5% to 10%.

[0024] The present invention provides a lubricant composition, comprising a solid lubricant and a liquid lubricant. By controlling the water contact angle of the solid lubricant, the solid lubricant has suitable hydrophobic properties. When combined with a liquid lubricant having a specific extreme pressure lubrication coefficient, the adhesion of the liquid lubricant in the water phase environment to the surface of the hydrophobic solid lubricant can be enhanced to exert the solid-liquid synergistic lubrication performance. The lubricant composition of the present invention has the advantages of high temperature resistance, high pressure resistance, resistance to saturated salt pollution, etc., and can significantly reduce the extreme pressure lubrication coefficient of the drilling fluid. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 This is a scanning electron microscope image of the modified graphite in Example 1 of the present invention at a magnification of 1500 times;

[0027] Figure 2 This is a scanning electron microscope image of the graphite in Example 1 of the present invention at a magnification of 1500 times. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The first aspect of the present invention provides a lubricant composition, comprising a solid lubricant and a liquid lubricant, wherein the water contact angle of the solid lubricant is greater than 90°;

[0030] The extreme pressure lubrication coefficient of the liquid lubricant is less than 0.15.

[0031] After the solid lubricant is adsorbed on the friction pair interface, a pit structure can be constructed. On the one hand, the pit structure can store liquid lubricants. Under extreme pressure conditions, the surface of the drill bit contacts the convex body, forming a closed space for the liquid lubricant. The liquid lubricant is stored in the above-mentioned closed space, thereby preventing the liquid lubricant from overflowing from the friction pair surface under extreme pressure. Using the above method, the occurrence stability of the lubricant composition at the friction pair interface under high temperature and extreme pressure conditions can be comprehensively improved, and the friction between the drill bit and the formation can be converted into fluid lubrication inside the infiltrated liquid phase lubricant and between the solid lubricant.

[0032] The water contact angle of the solid lubricant is controlled to be greater than 90°. When the solid lubricant is adsorbed on the friction pair interface, the wettability of the friction pair interface is adjusted to be hydrophobic and oleophilic, which can prevent the water phase in the drilling fluid from entering the friction pair interface. The water lubrication performance of the water phase is poor. By inhibiting the water phase from entering the friction pair interface, the lubrication performance of the lubricant can be improved; the extreme pressure lubrication coefficient of the liquid lubricant is less than 0.15, and it has good lubricity. When the solid lubricant is combined with the liquid lubricant, the solid phase lubricant can self-assemble and adsorb on the friction pair interface through hydrophobic action to construct a hydrophobic and oleophilic interface, which can effectively improve the adsorption stability of the oil phase lubricant on the above interface, increase the thickness of the lubricating film, and significantly improve the lubrication effect.

[0033] In a specific implementation, the roughness of the solid lubricant is 10-400 nm.

[0034] By limiting the roughness of the solid lubricant, the solid lubricant can have good hydrophobic and oleophilic properties. The modified graphite is adsorbed on the interface of the friction pair, which makes it difficult for the water phase to adsorb on the interface, and has a hydrophobic effect; at the same time, the modified graphite has a strong oleophilicity, and the oil phase lubricant can penetrate into the concave pores on the surface of the modified graphite, which can improve the adsorption stability of the oil phase lubricant on the interface, thereby improving the comprehensive lubrication performance of the lubricant composition.

[0035] In a specific embodiment, the surface energy of the solid lubricant is less than 54.8 mN·m.

[0036] When the surface energy of the solid lubricant is less than 54.8 mN·m, the solid lubricant has hydrophobic properties. The lower the surface energy, the better the hydrophobic and oleophilic effects. The lubricating properties of the lubricant composition can be improved by enhancing the adsorption stability of the oil phase lubricant at the friction pair interface.

[0037] In a specific embodiment, the solid lubricant is modified graphite, and the modifier includes at least one of hydroxyl-containing nanoparticles and a silane coupling agent.

[0038] Modified graphite serves as the skeleton of the super-wetting layer of the liquid lubricant. Its strong rigidity can improve the pressure resistance of the lubricating layer. Furthermore, when friction occurs during relative movement between the drill bit and the formation, the lubricant stored in the pit produces a dynamic pressure effect, which can effectively resist external high pressure. The liquid lubricant is stored in the pit and moves with the friction pair. The liquid lubricant moves from the bottom of the pit to the edge of the pit. In the wedge-shaped structure at the edge of the pit, the liquid lubricant is compressed and generates a reverse force, which is micro-dynamic pressure. A large amount of micro-dynamic pressure accumulates to produce a higher dynamic pressure, which can effectively resist external high pressure, allowing the interface of the surface texture to withstand extreme environments such as extreme pressure, friction and external impact.

[0039] The hydroxyl-containing nanoparticles can be formed by hydrolysis of tetraethyl orthosilicate or metatitanic acid.

[0040] The silane coupling agent includes at least one of an alkyl silane coupling agent, a fluorocarbon silane coupling agent, and a silicone ether silane coupling agent.

[0041] Furthermore, the hydroxyl-containing nanoparticles are formed by hydrolyzing tetraethyl orthosilicate; and the silane coupling agent is an octadecyl silane coupling agent.

[0042] When the modifier is one of hydroxyl-containing nanoparticles and silane coupling agents, the modified graphite can be prepared by a preparation method including the following process:

[0043] dispersing graphite and a cationic surfactant in a solvent to obtain a graphite dispersion;

[0044] The pH of the graphite dispersion is adjusted to 10-11 and the temperature is adjusted to 40-60° C., and hydroxyl-containing nanoparticles or silane coupling agents are added to react for 4-6 hours.

[0045] The above solvent is a conventional solvent in the art, for example, water, ethanol or a mixed solution of the two.

[0046] When the modifier is a hydroxyl-containing nanoparticle and a silane coupling agent, the modified graphite can be prepared by a preparation method including the following process:

[0047] dispersing graphite and a cationic surfactant in a solvent to obtain a graphite dispersion;

[0048] The pH of the graphite dispersion is adjusted to 10-11 and the temperature is adjusted to 40-60° C., and hydroxyl-containing nanoparticles are added to react for 4-6 hours.

[0049] The pH of the above solution is adjusted to 10-11, the temperature is adjusted to 40-60° C., a silane coupling agent is added, and the reaction is carried out for 4-6 hours.

[0050] Modifying graphite with a modifier can increase the roughness of graphite and reduce the surface energy of graphite.

[0051] In a specific embodiment, the mass ratio of the graphite, the cationic surfactant, the hydroxyl-containing nanoparticles, and the silane coupling agent is (8-10): (0.1-0.5): (0-2): (0-1).

[0052] By controlling the ratio of the above components, both the cost and the performance of the solid lubricant can be taken into account.

[0053] In a specific embodiment, the liquid lubricant includes a fatty acid derivative and a nonionic surfactant.

[0054] Liquid lubricants have certain surface activity, with the help of which, solid lubricants can be dispersed in drilling fluids. As the drilling fluid circulates underground, due to the increase in formation temperature, the solid lubricants will spontaneously separate from the water phase under the hydrophobic effect and adsorb to the friction pair interface, adjusting the wettability of the underwater friction pair interface to underwater super-oleophilicity, which is conducive to capturing the liquid lubricant containing fatty acid derivatives, constructing a liquid lubricant super-wetting layer, and improving the storage stability of the lubricant composition.

[0055] In a specific embodiment, the mass ratio of the fatty acid derivative to the nonionic surfactant is (30-80):(20-70).

[0056] Through the above combination and ratio, the liquid lubricant can have good lubricating performance.

[0057] Further, in a specific embodiment, the fatty acid derivative includes at least one of fatty acid esters, fatty acid amides, sulfurized fatty acid esters, sulfurized fatty acid amides, fatty acid amide phosphates, fatty acid polyoxyethylene ethers, and fatty acid polyoxypropylene ethers;

[0058] And / or, the nonionic surfactant includes at least one of Span 80 and Tween 80.

[0059] Specifically, the fatty acid derivative is a mixture of fatty acid methyl ester and sulfonated fatty acid methyl ester; the nonionic surfactant includes Span 80;

[0060] Furthermore, the mass ratio of fatty acid methyl ester, sulfonated fatty acid methyl ester and Span 80 is (40-70):(10-30):(20-70).

[0061] It can be understood that, in a specific embodiment, the lubricant composition further comprises at least one of mineral oil and thickener;

[0062] The volume proportion of the mineral oil in the lubricant composition is 10% to 50%;

[0063] The mass proportion of the thickener in the lubricant composition is 1% to 5%.

[0064] The present invention does not impose too many restrictions on mineral oil, and conventional materials in the art, such as white oil, can be used. Adding mineral oil to the lubricant composition can reduce the amount of liquid lubricant used and reduce costs.

[0065] The thickener includes at least one of paraffin wax and organic clay. Adding the thickener can increase the viscosity of the lubricant composition and make the solid lubricant and the liquid lubricant dispersed evenly and more stably.

[0066] A second aspect of the present invention provides a drilling fluid, comprising the lubricant composition and conventional drilling fluid.

[0067] Conventional drilling fluid refers to drilling fluid without the addition of lubricants.

[0068] A method for preparing drilling fluid comprises the following steps: mixing the lubricant composition and conventional drilling fluid.

[0069] Furthermore, the mass ratio of the lubricant composition to the conventional drilling fluid is 0.5% to 10%.

[0070] The solution provided by the present invention is further described below in conjunction with specific embodiments.

[0071] Example 1

[0072] 1) Add 10g of graphite and 0.1g of hexadecyltrimethylammonium chloride to 100mL of deionized water / ethanol (1:1) mixed solvent and stir evenly. Add ammonia water to adjust the pH value to about 10;

[0073] 2) Add 2 g of ethyl orthosilicate dropwise to the above solution under stirring at 60° C. and react for 6 h;

[0074] 3) Maintaining 60°C and continuing stirring, 0.5 g of octadecyltrimethoxysilane was added dropwise to the above solution, and ammonia water was added to control the pH value to between 10, and the reaction was continued for 6 hours;

[0075] 4) drying and grinding the solid phase suspension in 3) to obtain a solid phase lubricant;

[0076] 5) Methyl oleate, Span 80 and sulfurized methyl oleate are compounded in a ratio of 40:50:10 to form a liquid lubricant;

[0077] 6) Mix the solid lubricant, liquid lubricant and white oil in the following volume ratio: 20:70:10.

[0078] Add 1% paraffin and stir at 60°C for 1 hour to obtain a lubricant composition.

[0079] The modified graphite (i.e. solid phase lubricant) and graphite were analyzed by scanning electron microscope. The results are as follows Figure 1 and Figure 2 .

[0080] It can be seen from the figure that the surface of the modified graphite becomes rougher, making it more hydrophobic.

[0081] Example 2

[0082] This embodiment is basically consistent with Embodiment 1, except that the solid phase lubricant is graphite.

[0083] Example 3

[0084] This embodiment is basically consistent with Embodiment 1, except that Span 80 is replaced by Tween 80.

[0085] Example 4

[0086] This embodiment is basically the same as the embodiment 1, except that methyl oleate, Span 80 and methyl oleate sulfide are compounded in a ratio of 70:20:10.

[0087] Example 5

[0088] This embodiment is basically the same as the embodiment 1, except that methyl oleate, Span 80 and methyl oleate sulfide are compounded in a ratio of 20:70:10.

[0089] Example 6

[0090] This embodiment is basically consistent with the embodiment 1, except that the modifier is only ethyl orthosilicate, and no octadecyltrimethoxysilane is present, that is, step 3 is missing.

[0091] Example 7

[0092] This embodiment is basically consistent with the embodiment 1, except that: the modifier is only octadecyltrimethoxysilane, and there is no ethyl orthosilicate, that is, step 2 is missing.

[0093] Comparative Example 1

[0094] The lubricant provided in this comparative example is graphite.

[0095] Comparative Example 2

[0096] The lubricant provided in this comparative example is the solid phase lubricant prepared by steps 1) to 4) in Example 1.

[0097] Comparative Example 3

[0098] The lubricant provided in this comparative example is a product obtained by mixing the liquid lubricant prepared in step 5) in Example 1 with white oil in a volume ratio of 90:10, adding 1% paraffin, and stirring at 60° C. for 1 hour.

[0099] Test example

[0100] 1. The water contact angle, roughness and surface energy of the solid lubricant in the lubricant composition of the embodiment and the comparative example were tested, and the extreme pressure lubrication coefficient of the liquid lubricant was tested.

[0101] Test method for water contact angle: The solid phase lubricants in the examples and comparative examples are pressed into sheets using a tablet press, and the contact angle of deionized water on the surface of the sheet-like solid phase lubricant is tested using a contact angle meter.

[0102] Roughness test method: Use a profile measuring instrument to test the surface roughness of the solid phase lubricant.

[0103] Surface energy testing method: Using water and n-hexadecane as test liquids, the Owens two-liquid method is used to test the surface energy of the solid phase lubricant.

[0104] Test method of extreme pressure lubrication coefficient: Use extreme pressure lubrication instrument to test the extreme pressure lubrication coefficient of the liquid lubricant synthesized in the embodiment and comparative example in a water phase containing 4% bentonite, and the lubricant addition amount is 1%. See the extreme pressure lubrication performance evaluation section below.

[0105] The test results are shown in Table 1.

[0106] Table 1 Relevant properties of lubricant compositions in Examples and Comparative Examples

[0107]

[0108]

[0109] 2. Evaluation of extreme pressure lubrication performance

[0110] The lubricants prepared in the examples and comparative examples were tested for their extreme pressure lubrication coefficients before and after aging at 180° C. in the drilling fluid.

[0111] The specific operation is: prepare the density of 2.0g / cm according to the following formula 3 Drilling fluid: 2% bentonite + 3% DSP-1 + 5% SPNH + 10% KCl + 0.3% NaOH + barite. Add 5% of the lubricant composition in Example 1 to the above drilling fluid system and stir at high speed for 20 minutes. Then, heat-roll age the drilling fluid with lubricant added in a roller furnace at 180°C for 16 hours.

[0112] The processing steps of the remaining embodiments and comparative examples refer to the steps of the above-mentioned embodiment 1. Among them, the graphite product in comparative example 2 is difficult to be evenly dispersed in the water phase due to its strong hydrophobicity, and 1% Span 80 needs to be added to help it disperse in the water phase.

[0113] Extreme pressure lubrication performance test: Fann 21200 extreme pressure lubrication instrument was used to test the extreme pressure lubrication coefficient of the drilling fluid system before and after aging. The test ring speed was 60 rpm and the applied torque was 150 inch-pounds.

[0114] Table 2 Extreme pressure lubrication performance evaluation

[0115]

[0116]

[0117] 3. Evaluation of lubrication performance of high-density drilling fluid

[0118] Drilling fluids of different densities were prepared according to the following formula: 2% bentonite + 3% DSP-1 + 5% SPNH + 10% KCl + 0.3% NaOH + barite. The lubricant composition in Example 1 was added to drilling fluids of different densities, and the test results are shown in the following table. The aging temperature was 180°C and the aging time was 16h.

[0119] Table 3 High pressure resistance performance evaluation

[0120]

[0121] 4. Evaluation of high temperature and high salt resistance

[0122] The drilling fluid base slurry was prepared according to the following formula: 4% bentonite + 0.3% NaCO3, and a certain amount of salt (NaCl) was added. The lubricant composition in Example 1 was tested at different aging temperatures and salt concentrations. The test results are shown in the following table. The density of the drilling fluid is 2.0 g / cm 3 .

[0123] Table 4 Evaluation of high temperature resistance and high salt resistance

[0124]

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lubricant composition, characterized in that: It comprises a solid lubricant and a liquid lubricant, wherein the water contact angle of the solid lubricant is greater than 90°; The extreme pressure lubrication coefficient of the liquid lubricant is less than 0.

15.

2. The lubricant composition according to claim 1, characterized in that The roughness of the solid lubricant is 10-400 nm.

3. The lubricant composition according to claim 1 or 2, characterized in that The surface energy of the solid lubricant is less than 54.8 mN·m.

4. The lubricant composition according to any one of claims 1 to 3, characterized in that The solid lubricant is modified graphite, and the modifier includes at least one of hydroxyl-containing nanoparticles and a silane coupling agent.

5. The lubricant composition according to any one of claims 1 to 4, characterized in that The liquid lubricant includes fatty acid derivatives and nonionic surfactants.

6. The lubricant composition according to claim 5, characterized in that The fatty acid derivatives include at least one of fatty acid esters, fatty acid amides, sulfurized fatty acid esters, sulfurized fatty acid amides, fatty acid amide phosphates, fatty acid polyoxyethylene ethers, and fatty acid polyoxypropylene ethers; And / or, the nonionic surfactant includes at least one of Span and Tween.

7. The lubricant composition according to any one of claims 1 to 6, characterized in that Also includes at least one of mineral oil and thickener; The volume proportion of the mineral oil in the lubricant composition is 10% to 50%; The mass proportion of the thickener in the lubricant composition is 1% to 5%.

8. The lubricant composition according to claim 4, characterized in that The modified graphite is prepared by a preparation method comprising the following processes: dispersing graphite and a cationic surfactant in a solvent to obtain a graphite dispersion; The pH of the graphite dispersion is adjusted to 10-11 and the temperature is adjusted to 40-60° C., and hydroxyl-containing nanoparticles and / or silane coupling agents are added to react for 4-6 hours.

9. The lubricant composition according to claim 8, characterized in that The mass ratio of the graphite, the cationic surfactant, the hydroxyl-containing nanoparticles and the silane coupling agent is (8-10): (0.1-0.5): (0-2): (0-1).

10. A drilling fluid, characterized in that: The invention comprises the lubricant composition according to any one of claims 1 to 9 and conventional drilling fluid.